The Influence of Perceived Value on Repurchase Intention with the Mediation of Trust and Brand Image in the Whoosh Transportation Mode - Ahmad Zaki Pratama; Kusuma Ratnawati; Sri Palupi Prabandari (Greenation International Journal of Economics and Accounting, 2026)
This study aims to analyze the influence of perceived value on repurchase intention toward the Whoosh transportation service, with trust and brand image acting as mediating variables. The research is motivated by fluctuations in the number of Whoosh passengers, indicating that the initial public interest has not fully transformed into sustainable repurchase intention. This study applies a quantitative approach with an explanatory research design. Data were collected from 261 respondents consisting of active users, former users, and potential users of Whoosh services in the Jakarta–Bandung area. The sampling technique employed was purposive sampling, while data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived value has a positive and significant effect on repurchase intention, trust, and brand image. In addition, trust and brand image also positively influence repurchase intention. The mediation analysis further demonstrates that trust and brand image significantly mediate the relationship between perceived value and repurchase intention. These findings suggest that enhancing customer-perceived value through service quality, operational reliability, and strengthening the modern image of Whoosh can increase public trust and encourage sustainable repurchase intention toward the service.